Grieving for Pigeons Twelve Stories of Lahore - Ahmad, Zubair (Mingling Voices, 2022)
In this poignant and meditative collection of short stories, Zubair Ahmad captures the lives and experiences of the people of the Punjab, a region divided between India and Pakistan. In an intimate narrative style, Ahmad writes a world that hovers between memory and imagination, home and abroad. The narrator follows the pull of his subconscious, shifting between past and present, recalling different eras of Lahore's neighbourhoods and the communities that define them. These stories evoke the complex realities of post-colonial Pakistani Punjab. The contradictions of this region's history reverberate through the stories, evident in the characters, their circumstances, and sometimes their erasure. Skillfully translated from Punjabi by Anne Murphy, this collection is an essential contribution to the wider recognition of the Punjabi language and its literature.